Perlindungan Data Privasi Pasien Remaja dalam Layanan Kesehatan Reproduksi di Klinik Pratama Mardi Saras: Antara Etika Medik dan Regulasi Nasional - Rifki Rifki (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Adolescents face significant barriers in accessing reproductive health services due to fears of privacy breaches and social stigma. In primary healthcare facilities, healthcare professionals are often trapped in a dilemma between the obligation to maintain medical confidentiality based on professional ethics and national regulatory demands requiring parental involvement for underage patients. This study aims to analyze the practice of protecting adolescent patient data privacy at Mardi Saras Primary Clinic and identify the gap between practical implementation and the norms of medical ethics and applicable legal regulations. This study employs a socio-legal research method with a qualitative approach. Data were collected through in-depth interviews with doctors and nurses, observation of service procedures, and study of the clinic's Standard Operating Procedures. The results indicate that although Mardi Saras Primary Clinic has implemented basic confidentiality protocols such as closed consultation rooms, there are substantial weaknesses in informed consent management, which still heavily relies on parental presence for all adolescent cases. This practice is driven by healthcare professionals' fear of legal risks, thereby ignoring the principle of developing autonomy in adolescents. These findings indicate a disparity between rigid administrative compliance and the spirit of protecting adolescent health rights within national regulations. The implication of this study underscores the urgency of developing specific SOPs that are sensitive to adolescent rights, as well as the need for continuous training for healthcare professionals regarding the legal and ethical boundaries of maintaining confidentiality for underage patients without compromising legal safety aspects.